Relation of Elevated Serum AFP Levels with Preterm Labor in Kirkuk City-Iraq - Noorjan Qasim Ahmed1 , Maysaa Abdalhussein Mohammed2 , Shaimaa Mohammed Sulaiman3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study conducted in Kirkuk city in the period from February 2017 to the end of December 2017, which included 100 pregnant women who had regular contractions and/or short cervical cervices between 24 to 32 weeks of pregnancy and 100 healthy controls who did not suffer from complications Pregnancy and they were delivered on time. For the purpose of comparing the two groups with respect to the level of AFP. The study included collecting blood samples from both groups prior to birth to investigate and measure the level of the protein AFP in their blood. The study demonstrated that the lowest mean of cervical length and birth Wight were found in group with preterm labor as compared with the control group. The study revealed that the mean of AFP was elevated significantly in women with preterm delivery (17.7±2.11 pg/ml) as compared with the control group (8.23 ±1.67 pg/ml) at P. value <0.05. In this study, 40 of 100 of study cases delivered preterm (< 34 weeks).. The study found positive correlation of serum AFP with birth weight, birth head during 1st and 5th weeks of delivery (p< 0.01).